RANCANG BANGUN ALAT PEMBERI PAKAN IKAN DENGAN SISTEM AUTOMATISASI BERBASIS ARDUINO UNO R3 DENGAN SISTEM KENDALI SMS - Ardiwijoyo, Ardiwijoyo; Jamaluddin P, Jamaluddin P; Mappalotteng, Abdul Muis (Universitas Negeri Makassar, 2018)
The aim this study to make the design of fish feeding device that autometically based Arduino Board that can be applied in fish pond and to implement the design of fish feeding device that autometically for fish cultivation. The method used in the study in Research and Development (R & D), the result of research processed used quantitative data analysis techniques with several mechanisms such as made a framework, the installation of material components and manufacturing of microcontroller systems which includes making the path of series, the installation of components and inputting language program in microcontroller system. The device of fish feeding based mirocontroller can not be effective and effecient if compared with feeding manually that done by human.